Male or Female Sexual Identity in Adolescence - Márquez Barradas, María Luz; Pérez Rosiles, Lourdes; Sibaja Terán, Beatriz (Revista de Psicología, 2004)
Young people express a sexual liberalism more discursive than practical. This paper shows that their attitudes continue being highly conservative. From a high school sample, data about their opinion and assessmente of some questions referred are compared in order to denote the differences among them.